2014
DOI: 10.3389/fncom.2014.00086
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium dynamics permit a Purkinje neuron model to perform toggle and gain computations upon its inputs

Abstract: Without synaptic input, Purkinje neurons can spontaneously fire in a repeating trimodal pattern that consists of tonic spiking, bursting and quiescence. Climbing fiber input (CF) switches Purkinje neurons out of the trimodal firing pattern and toggles them between a tonic firing and a quiescent state, while setting the gain of their response to Parallel Fiber (PF) input. The basis to this transition is unclear. We investigate it using a biophysical Purkinje cell model under conditions of CF and PF input. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 68 publications
(135 reference statements)
2
21
0
Order By: Relevance
“…GABAergic inhibition generated by cerebellar interneurons locally modifies the conductance changes and Ca 2ϩ fluxes evoked by climbing fiber input (Callaway et al, 1995;Kitamura and Häusser, 2011). Decreases in gain occur following a CS when high Ca 2ϩ levels reduce parallel fiber input by activation of BK channels and/or endocannabinoid release (Brenowitz and Regehr, 2003;Rancz and Häusser, 2010) and modeling suggests that gain increases occur with local increases in Ca 2ϩ (Forrest, 2014). These same sources of variability in the response to climbing fiber input determine whether long-term facilitation or depression results at parallel fiber-Purkinje cell synapses (Coesmans et al, 2004;Medina and Lisberger, 2008;Rasmussen et al, 2013).…”
Section: Bidirectional Changes In Ss Encodingmentioning
confidence: 99%
“…GABAergic inhibition generated by cerebellar interneurons locally modifies the conductance changes and Ca 2ϩ fluxes evoked by climbing fiber input (Callaway et al, 1995;Kitamura and Häusser, 2011). Decreases in gain occur following a CS when high Ca 2ϩ levels reduce parallel fiber input by activation of BK channels and/or endocannabinoid release (Brenowitz and Regehr, 2003;Rancz and Häusser, 2010) and modeling suggests that gain increases occur with local increases in Ca 2ϩ (Forrest, 2014). These same sources of variability in the response to climbing fiber input determine whether long-term facilitation or depression results at parallel fiber-Purkinje cell synapses (Coesmans et al, 2004;Medina and Lisberger, 2008;Rasmussen et al, 2013).…”
Section: Bidirectional Changes In Ss Encodingmentioning
confidence: 99%
“…9-11. In the temporal coding scheme, information is not only encoded in the timing and duration of spiking, but also in the timing and duration of non-spiking (quiescent) 29,30 . In our system, short and long spiking times (t ss and t sl ) in the PSC signal (Supplementary Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The up state is characterised by high simple spike rates whereas in the down state simple spiking is quiescent. Several models of Purkinje cell activity have attempted to describe this bimodality (Forrest, 2014;Forrest et al, 2012;Llinas and Sugimori, 1980b;Loewenstein et al, 2005;McKay et al, 2007;Williams et al, 2002). Combined theoretical and experimental work has shown that Purkinje cells exhibit a phenomenon known as inverse stochastic resonance.…”
Section: Discussionmentioning
confidence: 99%